Outcomes of Open Retro-Rectus Hernia Repair With Mesh in Obesity Class III. Issue 9 (September 2020) - Martinez, Manuel; Dove, James; Blansfield, Joseph; Widom, Kenneth; Semian, John; Alaparthi, Mohanbabu; Factor, Matthew
Background: Abdominal wall hernias continue to be one of the most common general surgery pathologies. Patients with an elevated body mass index (BMI) are routinely counseled about weight loss before elective repair. However, a definitive BMI "cutoff" has not been established. Here, we report our experience with open retro-rectus hernia repair (ORRHR) with mesh in patients with a BMI over 40 kg/m 2, and we attempt to determine if a BMI "cutoff" can be established. Methods: Data from patients undergoing ORRHR with mesh at Geisinger Medical Center from January 1, 2014, to December 31, 2018, were collected and retrospectively analyzed. Results: Cohorts were composed of 2 groups, BMI ≥ 40 kg/m 2 (n = 117) and BMI < 40 kg/m 2 (n = 90). All patients underwent an elective ORRHR with mesh. Operative time increased significantly as the patient's BMI increased ( P ≤ .01). Patients in the higher BMI group had a significantly higher rate of surgical site infections (SSIs) (8.55% vs. 1.1%, P = .018). Higher BMI did not translate to a higher recurrence rate. Conclusions: Patients undergoing ORRHR with mesh who had a BMI over 40 kg/m 2 had an increased risk of SSI and longer operative time, possibly suggesting a potential association other than SSI and BMI. More studies are needed to determine if BMI is indeed correlated with hernia recurrence and if BMI should influence the decision to undergo repair.